(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2006)
In this paper we describe Hopf point analysis for several systems of ordinary and time delay differential equations which encode the most important assumptions concerning anguigenesis processes induced by tumours It is shown that in most cases Hopf points exist only if time delays are nonzero and for most nonzero time delays there are Hopf points in these families of models.